DIRECTIVE SPEECH ACTS IN HUMOROUS DISCOURSE ON YOUTUBE CHANNEL: WARINTIL OFFICIAL AS CASE STUDY - Muhammad Saiful Mukminin (Universitas Sebelas Maret, 2024)
Directive speech act is a type of speech act that can give influence to others. In humor discourse, directive speech acts can appear through forms of language use used by speakers to speech partners. The purpose of this study is to describe the form of directive speech acts and its most dominant form in YouTube Channel 'Warintil Official' videos. This research applies descriptive qualitative research paradigm. The data in this study are utterances containing directive forms spoken by the actors in the 'Warintil Official' video. The data collection techniques used are the observation method with free participant observation, recording technique, and note-taking. Data analysis consists of three stages, namely data reduction, data presentation, and conclusion drawing. The result of this research shows that there are eight forms of directive speech acts, namely ordering, commanding, requesting, asking, recommending, prohibitives, permissives, and advising. The most dominant directive speech act in this study is asking. It shows that the speaker needs information from the speech partner